PERAN GURU DALAM MENANAMKAN KEDISIPLINAN SISWA DI MADRASAH IBTIDAIYAH - Aurora, Farida Nur; Rofi'ah, Siti; Fatichatul Zulva, Nina (PGMI UNHASY, 2025)
Discipline is an essential aspect of shaping students character and an integral part of Islamic Education. Using a descriptive qualitative method, this tudy examines teachers strategies in implementing discipline in the classroom through observation, intevriews, and documentation. The subjects of this research are first grade students at MISS Seblak Jombang. The findings indicate that teachers serve as primary role models in fostering students discipline through exemplary behavior, clear rule enforcement, and a persusive approach rooted in Islamic values. Additionally, teachers implement disciplinary strategies, including routine habituation, educational reward and punishment systems, and effective communication with students and parents. The challenges identified in this process include inconsistencies in rule enforcement and the diverse backgorunds of students, which influence their level of discipline. Therefore, a more holistic and collaborative approach between teachers, schools, and parents is needed to instill sustainable discipline values. This study provides insight into the significant role of teachers in cultivating aculture of discipline within the madrasah Ibtidaiyah environment.